Career Succession Planning in the Family Business - Rutar, Tjaša; Logar, Matic (Izzivi prenosa vodenja na naslednjo generacijo v družinskem podjetju, 2025)
The aim of this chapter is to explore the key factors of successful succession in a family business, focusing on the impact of career planning, organisational climate and the personal motivation of successors. The scope of the research covers leadership transition within Slovenian family businesses, with a case study of Dines d.o.o. Methodologically, the work is based on a qualitative approach, conducted through an in-depth semi-structured interview with the successor. Four hypotheses were analysed, testing the importance of formalised procedures, organisational climate, motivation and rules in reducing conflicts. The findings show that successful leadership transition is not necessarily conditioned by formal structures, but is significantly more supported by trust, early involvement of the successor and open communication. The hypotheses on the influence of organisational climate and successor motivation are fully supported, while formalisation proves to be less decisive. The conclusions underline the importance of the human factor in succession and recommend the early involvement of successors, the creation of a supportive climate and the development of strategies that take into account the specific characteristics of each company.